PENGARUH PERILAKU BELAJAR SISWA DAN KECERDASAN EMOSIONAL TERHADAP STRES MENGHADAPI UJIAN NASIONAL PADA MATA PELAJARAN AKUNTANSI MADRASAH ALIYAH DI KABUPATEN TUBAN - Sudjatmiko, Bagus; Kurnia, Kurnia; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research was conducted with the aim of analyzing whether there is influence student behavior and emotional intelligence to stress in the face of national exam accounting subjects. The results showed that: behaviors of student learning and emotional intelligence gives significant influence on the national exams stress on accounting subjects. If the students learning behavior and emotional intelligence lead to increased stress on the face national exam accounting subjects decreased, and vice versa.Keywords: Behavioral learning, emotional intelligence, stress exams